Generic Preoperative Planning for Proximal Femoral Osteotomy in the Treatment of Nonunion of the Femoral Neck. (February 2018) - Mayo, Keith; Kuldjanov, Djoldas
Abstract : Summary: Despite improvements in surgical technique and overall patient care, failed treatment of fractures of the femoral neck persists. For the physiologically young patient, joint preservation is the preferred method of treatment. Unfortunately, the best treatment option, proximal femoral osteotomy, is fast becoming a lost art. Preoperative planning is critical in this regard. The described preoperative planning work flow is a reliable method for obtaining the desired deformity correction for a variety of proximal femoral malunions and nonunion. Revisiting the classic Pauwels osteotomy for femoral neck nonunion is an appropriate vehicle to supply the first link in resurrecting this treatment modality by providing a standardized preoperative planning protocol.